Legal Analysis Of Mediation In The Settlement Of Joint Property Disputes In Marriage In Terms Of Islamic Law And Positive Law - gideon gideon; gideon gideon (UIN Siber Syekh Nurjati Cirebon, 2024)
Joint Property has become a polemic in Indonesia’s Islamic legal discourse and legal system. Initially, the assets brought by the husband did not have any identification, nor did those brought by the wife. Such assets are inherited assets of both parties, which are identified as the personal property of the husband or wife. The assets a husband and wife produce during marriage are a logical consequence of marriage. The aim of this research is firstly to find out more about Islamic law regarding mediation in resolving marital property disputes. Secondly, I want to find out more about the positive legal review of mediation in resolving marital property disputes. This research was conducted using a Normative Juridical approach. The specifications of this research are descriptive analysis. The conclusion that can be obtained is that mediation in the distribution of joint property in Islamic law has no specific rules but only provides general guidelines for resolving joint property problems without causing disputes. Second, Supreme Court Regulation (PERMA) Number 1 of 2016 concerning Mediation Procedures in Court makes mediation part of the court process. In court to obtain peaceful efforts through the mediation process as contained in the Procedural Law Article 130 HIR or Article 154 RBg.